2006
DOI: 10.1161/01.str.0000221702.75002.66
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Stroke Incidence in the US Elderly

Abstract: Background and Purpose-This study assesses the effect of socioeconomic status on stroke incidence in the elderly, and the contribution of risk factors to stroke disparities. Methods-Data comprised a sample of 2812 men and women aged 65 years and over from the New Haven cohort of the Established Populations for the Epidemiologic Studies of the Elderly. Individuals provided baseline information on demographics, functioning, cardiovascular and psychosocial risk factors in 1982 and were followed for 12 years. Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
149
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 30 publications
12
149
4
1
Order By: Relevance
“…23 Such apparent differential vulnerability could be a consequence of clustering and mutual interaction between other active determinants. 24 Although others have described the important role of smoking and hypertension as contributors to the social gradients in stroke, [9][10][11][12] our data indicated only sparse differential exposure to hypertension across socioeconomic groups. Likewise, in previous trend studies during the 1980s and 1990s, no marked socioeconomic differences in blood pressure have been reported.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…23 Such apparent differential vulnerability could be a consequence of clustering and mutual interaction between other active determinants. 24 Although others have described the important role of smoking and hypertension as contributors to the social gradients in stroke, [9][10][11][12] our data indicated only sparse differential exposure to hypertension across socioeconomic groups. Likewise, in previous trend studies during the 1980s and 1990s, no marked socioeconomic differences in blood pressure have been reported.…”
Section: Discussionmentioning
confidence: 59%
“…7,8 The mechanisms driving social inequality in stroke have been described as being partly a result of differential exposure to well-established risk factors, such as hypertension and smoking, during a life course. [9][10][11][12] In previous studies, authors have suggested that smoking has a larger effect on ischemic stroke, hemorrhagic stroke, and heart disease if high blood pressure is also present. 3,5,[13][14][15] However, much less attention has been given to the extent to which these risk factors interact with socioeconomic exposures.…”
mentioning
confidence: 99%
“…We then divided our sample into three equally sized groups (tertiles) according to this score; the first tertile (score: ,4) was termed 'low SES', the second tertile was 'medium SES' (score: 4-10) and the third tertile was 'high SES' (score: .10). This type of assessment of SES has already been used in the literature (30) and it is not unusual in the quantification of SES for only one or two of its components (education, income and occupation) to be combined (31,32) . Of course, education level and financial status in multi-adjusted models could also be independently used.…”
Section: Bioethicsmentioning
confidence: 99%
“…8,9 An association between depression and stroke was observed in women included in the Nurses' Health Study, but age-specific effects were not reported. 10 Important age group differences may therefore have been masked in previous studies where associations were not stratified by age.…”
mentioning
confidence: 99%